2019
DOI: 10.1111/jsr.12902
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use and sleep health in young adults

Abstract: Poor sleep health is associated with numerous health concerns, and sleep problems are exacerbated by cigarette smoking. Although rates of traditional tobacco use are declining, rates of electronic cigarette (e-cigarette) use are comparatively high and growing. Given that nicotine is a primary mechanism by which smoking negatively impacts sleep health, e-cigarette use may also be linked to poor sleep health; however, no research has investigated this association. Participants were 1,664 college students, 40.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
3
22
1
Order By: Relevance
“…Given nicotine's function as a stimulant, the use of nicotine products might be expected to delay sleep onset, particularly if used near bedtime. However, the present study as well as a previous study 25 observed no significant association with SOL. This may be due, in part, to the method of assessing e‐cigarette use.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Given nicotine's function as a stimulant, the use of nicotine products might be expected to delay sleep onset, particularly if used near bedtime. However, the present study as well as a previous study 25 observed no significant association with SOL. This may be due, in part, to the method of assessing e‐cigarette use.…”
Section: Discussioncontrasting
confidence: 74%
“…By comparison, only a handful of studies have examined the impact of e‐cigarette use on sleep health. Emerging work has found e‐cigarette users report poorer subjective sleep quality and increased use of sleeping medications compared with nonusers 25 . Importantly, overall sleep quality was significantly worse among e‐cigarette and combustible cigarette users compared with nonusers, highlighting a potentially deleterious effect of e‐cigarette use on sleep; further, these findings suggest that the adverse effects of e‐cigarettes are comparable to those of combustible cigarettes.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although previous studies suggested that smoking might be a contributing factor for insomnia, there were considerable differences among the results of studies [14,19,20]. Besides, most of the studies were cross-sectional studies, which couldn't re ect the sequential order and causal relationship between smoking and insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Brett et al. (2020), probably for the first time ever, conducted a questionnaire study via the internet to investigate the impact of electronic cigarette use on sleep in young adults. There is a growing concern regarding electronic cigarette use in the last years, because of reported severe side effects, so it seems timely to collect data on the impact of this kind of nicotine consumption.…”
mentioning
confidence: 99%